IR sensor readout devices with source input circuits - Sizov, F.F.; Reva, V.P.; Derkach, Yu.P.; Kononenko, Yu.G.; Golenkov, A.G.; Korinets, S.V.; Darchuk, S.D.; Filenko, D.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Silicon readout devices with input direct injection and buffered direct injection circuits and charge-coupled devices (CCD) multiplexers to be used with n⁺-p- or p⁺-n-photovoltaic (PV) multielement arrays were designed, manufactured and tested in T = 77…300 K temperature region. The on-chip testing switches attach the sources of direct injection transistors to the common load resistors to imitate the output signal of mercury cadmium telluride (MCT) photodiodes. The silicon readout devices for 2x64 n⁺-p- or p⁺-n - linear arrays and n⁺-p- 2x4x128(144) time-delay and integration (TDI) arrays with skimming and partitioning functions were manufactured by n- or p-channel MOS technology with buried channel CCD registers. The designed CCD readout devices are driven with four- or two-phase clocking pulses.